PENGARUH PERUBAHAN POLA PERIODE KERJA PERUSAHAAN MINYAK DAN GAS PT. XYZ DI SUMATERA SELAMA MASA PANDEMI COVID-19 TERHADAP KINERJA KARYAWAN - Dessy Dwiyanti (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
One of the impacts of the Covid-19 pandemic experienced by PT. XYZ is achange in the working period policy of its employees in an effort to prevent thetransmission of the Covid-19 virus. PT. XYZ itself is an oil and gas company inSumatra. The working period was originally 14 working days -14 holidays(14:14) to 21 working days - 21 days off (21:21). This research was conducted todetermine the effect of working period (21:21) on employee performancecompared to the work period (14:14) used previously at PT. XYZ. Field researchthrough a qualitative approach is the method used in this research where thedata collection method is carried out through interviews with several employees and supervisors of the operational division as well as direct observations in thefield. The results found that in the work period of (21:21) work fatigue, workerrors, and stress levels increase higher when compared to the (14:14) workperiod. PT. XYZ should immediately conduct an evaluation related to employeecomfort and safety in situations that require field workers to work in this (21:21)pattern, so the company does not experience many losses due to a decrease inthe performance of its employees.